A Comparison of Alternative Econometric Models of Quarterly Investment Behavior - Jorgenson, Dale W.; Hunter, Jerald; Nadiri, M. Ishag (Econometrica, 1970)
In this paper four alternative quarterly econometric models of investment behavior are fitted to a common set of data for individual manufacturing industries in the United States. Goodness of fit and absence of autocorrelation of errors are used as a basis for comparison of the performance of the alternative models. The econometric models are compared with each other and with alternative explanations of data on investment based on surveys of anticipated investment and on mechanical forecasting schemes. The four econometric models included in our study are those of Anderson [2], Eisner [15], Jorgenson and Stephenson [38], and Meyer and Glauber [46]. On the basis of our comparison, the ranking of the alternative models is as follows: (1) Jorgenson-Stephenson, (2) Eisner, (3) Meyer-Glauber, (4) Anderson. Anticipatory data give a better fit to data on investment expenditures than that provided by any of the econometric models. Mechanical forecasting schemes provide a fit that is superior to the Anderson and Meyer-Glauber models. These schemes are slightly inferior to the Eisner model and clearly inferior to the Jorgenson-Stephenson model. The alternative econometric models included in our comparison differ in specification of the time structure of the investment process and in the role ascribed to specific determinants of investment behavior. Both aspects of an econometric model affect its performance so that it is difficult to discriminate among alternative determinants of investment behavior on the basis of our results.